The Development Process of Islamic STEAM Activity Storybooks for Early Childhood - Metafisika, Kartika; Azizah, Reza Nur; Fitriyah, Fifi Khoirul (Universitas Nahdlatul Ulama Surabaya, 2022)
This study aims to design and develop an Islamic Science, Technology, Engineering, Art, and Mathematics (STEAM) Activity Storybook prototype, which is a storybook with STEAM learning activity content in it, and there is an integration between the concept of science and Islamic content. The Design Research with the Plomp Model went through the preliminary investigation, design, and construction phases. The preliminary investigation results showed that Kindergarten teachers did not understand the essential elements in the implementation of STEAM learning and still did not have adequate references and media for STEAM learning implementation. In the design phase, principles in developing the Islamic STEAM Activity Storybook for Early Childhood and criteria for STEM/STEAM learning-based storybooks were formulated before entering the construction phase. The storyboard is developed to determine the narrative, activity sheet, context, or description of the image on the specified book page in the construction phase. The whole process was put forward as a reference for developing the Islamic STEAM Activity Storybook for Early Childhood on other STEAM learning content. The results of this study can help teachers and parents to plan and implement STEAM learning with Islamic content for early childhood.